SU(2)CMB at high redshifts and the value of H0 - Hahn, Steffen; Hofmann, Ralf (Monthly notices of the Royal Astronomical Society, 2017)
We investigate a high-z cosmological model to compute the comoving sound horizon rs at baryon-velocity freeze-out towards the end of hydrogen recombination. This model assumes a replacement of the conventional cosmic microwave background (CMB) photon gas by deconﬁning SU(2) Yang-Mills thermodynamics, three ﬂavours of massless neutrinos (Nν = 3) and a purely baryonic matter sector [no cold dark-matter (CDM)]. The according SU(2) temperature-redshift relation of the CMB is contrasted with recent measurements appealing to the thermal Sunyaev-Zel’dovich effect and CMB-photon absorption by molecular rotation bands or atomic hyperﬁne levels. Relying on a realistic simulation of the ionization history throughout recombination, we obtain z∗ = 1693.55 ± 6.98 and zdrag = 1812.66 ± 7.01. Due to considerable widths of the visibility functions in the solutions to the associated Boltzmann hierarchy and Euler equation, we conclude that z∗ and zdrag overestimate the redshifts for the respective photon and baryon-velocity freeze-out. Realistic decoupling values turn out to be zlf,∗ = 1554.89 ± 5.18 and zlf, drag = 1659.30 ± 5.48. With rs(zlf, drag) = (137.19 ± 0.45) Mpc and the essentially model independent extraction of rsH0 = constant from low-z data in Bernal, Verde & Riess, we obtain a good match with the value H0 = (73.24 ± 1.74) km s−1 Mpc−1 extracted in Riess et al. by appealing to Cepheid-calibrated Type Ia supernovae, new parallax measurements, stronger constraints on the Hubble ﬂow and a reﬁned computation of distance to NGC 4258 from maser data. We brieﬂy comment on a possible interpolation of our high-z model, invoking percolated and unpercolated U(1) topological solitons of a Planck-scale axion ﬁeld, to the phenomenologically successful low-z CDM cosmology.